ANALISIS STRUKTUR MIKRO SINTAKSIS DALAM PIDATO PRESIDEN PRABOWO PADA RAPAT KOORDINASI NASIONAL TAHUN 2026 - Putu Septa Githa Apsari; I Wayan Pastika; I Nyoman Suparwa (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze the syntactic microstructure in President Prabowo's speech at the 2026 National Coordination Meeting. This study uses a qualitative descriptive approach to analyze the linguistic elements in President Prabowo Subianto's speech at the 2026 National Coordination Meeting of the Central and Regional Governments based on Teun A. van Dijk's Critical Discourse Analysis framework. Data were collected through the listening method with the free listening technique of conversation (SBLC) on speech videos accessed from the YouTube platform. The results of the analysis show that there is the use of active and passive sentence forms to convey messages. In the coherence aspect, there is a coherence of cause and effect, opposition, affirmation and time used to clarify the relationship within sentences and between sentences so that the content of the speech is easy to understand. In the pronoun aspect, there is the use of first-person pronouns "saya", "aku", "gue", "kami" and "kita", second-person pronouns "lu", "kau", and "kalian", third-person pronouns "beliau" and "mereka".